Ijtimoiy taraqqiyot va umumiy o’rta ta’lim muassalarida tarbiya fanini o’qitishning ilmiy metodik asoslari - Shaymanov Jamshidbek, Boltayeva Sabo, Badriddinov Shaxzod (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
It is devoted to the analysis of the scientific and methodological bases of social development and teaching of education in general secondary educational institutions. In this work, the role of the science of education in the educational process, its impact on social development, and the effectiveness of educational methods and methods are discussed. In the article, modern scientific-pedagogical approaches and methods, as well as innovative approaches necessary for the effective functioning of the educational system, are considered in teaching the science of education. The goal is the development of scientific methodical foundations in teaching the science of education and through them the successful implementation of the process of education in social life.